NON-DRUG TREATMENT OF IMMUNOLOGICAL DISORDERS IN THE ACUTE PERIOD OF ISCHEMIC STROKE - Ochilova D.O. (Central Asian Journal of Medical and Natural Science, 2023)
In order to study the effectiveness of reflexotherapy in correction of immunological disorders in an acute period of ischemic stroke, 45 patients were clinical and immunological examined (on the 2nd day of patients’s stay in hospital and 15 days after the beginning of the course of early rehabilitation). In the main group of patients (30 people), whose basic complex of rehabilitation measures was optimized by the inclusion of reflexotherapy, there was a significant improvement in a number of indicators of cellular and humoral immunity: reduction of leukocytes in peripheral blood (p˂0.05), an increase in lymphocyte count (p˂0.05), relative and absolute values of T-lymphocytes (CD3+) content (р˂0.01 and р˂0.05, respectively), immunoregulatory cells of T-helpers (CD4+) (р˂0.05), decrease in the number of B-lymphocytes to normal values (р˂0.01), and an increase in IgG level (р˂0.05). In the control group (15 people), where standard treatment was conducted, there was no pronounced dynamics of the indices. Thus, a comprehensive clinical and immunological study of the effectiveness of non-drug correction of immunological disorders in the acute period of ischemic stroke demonstrated high efficiency of acupuncture, with relative simplicity and safety of its application.